Comparative Study of Linguistic Register Between Two Region : A Review (International Journal of Scientific Research in Science and Technology, 2024)
Language Register is also called as Linguistic Register which determines how to express yourself in the set of Language Varieties in various ways with the help of vocabulary, formation, and some grammar. Language Register matters everywhere while communicating with another individual. In each type of register provides rich opportunities for content, topic, location including speech and writing activities. Differentiating the two relative major District’s Pune and Ahmednagar in Language Register. Why Pune district is most popular, education leading, opportunity oriented and Ahmednagar is less developed, culture oriented and cultivation.